COGNITIVE MECHANISMS OF MEANING CONSTRUCTION IN INFORMATION TECHNOLOGY TERMINOLOGY (KONFERENSIYA, 2026)
This article analyzes Information Technology (IT) terminology from a cognitive-linguistic perspective, emphasizing that technical terms function as tools of conceptualization rather than mere labels. Drawing on Conceptual Blending Theory and mental model theory, it shows how metaphor-based terms such as cloud and firewall help users understand abstract technological processes. The study also demonstrates that disciplinary and multilingual contexts shape terminological meaning, leading to semantic variation but also enhanced cognitive flexibility. The findings highlight the importance of cognitively informed terminology in education and interdisciplinary communication.